2024
DOI: 10.1101/2024.04.04.588169
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dietary protein source strongly alters gut microbiota composition and function

J. Alfredo Blakeley-Ruiz,
Alexandria Bartlett,
Arthur S McMillan
et al.

Abstract: The source of protein in a persons diet affects their total life expectancy. However, the mechanisms by which dietary protein sources differentially impact human health and life expectancy are poorly understood. Dietary choices have major impacts on the composition and function of the intestinal microbiota that ultimately mediate host health. This raises the possibility that health outcomes based on dietary protein sources might be driven by interactions between dietary protein and the gut microbiota. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 89 publications
1
1
0
Order By: Relevance
“…These included mucin 5B and alpha-1-acid glycoprotein in egg white and cell wall proteins in yeast. We previously showed that egg white and yeast protein diets impact the glycan metabolism of the gut microbiota 11,46 and now our results suggest that these specific glycoproteins may be involved in affecting microbiota glycan metabolism. In summary, our results show that dietary proteins from various sources with specific functional and structural features relevant to host physiology and microbial metabolism were differentially processed in the gut.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…These included mucin 5B and alpha-1-acid glycoprotein in egg white and cell wall proteins in yeast. We previously showed that egg white and yeast protein diets impact the glycan metabolism of the gut microbiota 11,46 and now our results suggest that these specific glycoproteins may be involved in affecting microbiota glycan metabolism. In summary, our results show that dietary proteins from various sources with specific functional and structural features relevant to host physiology and microbial metabolism were differentially processed in the gut.…”
Section: Discussionsupporting
confidence: 63%
“…While the exact mechanisms by which dietary protein from various sources impacts the host are not well understood, interactions between undigested dietary protein and the intestinal microbiota are thought to play a key role 7,8 . Specific dietary components, including dietary protein and fiber, have been shown to impact the composition and function of the gut microbiota [9][10][11] . Dietary proteins that escape host digestion can be converted by the gut microbiota to produce metabolites that impact host health, such as beneficial short-chain fatty acids or proinflammatory ammonia, amines, and hydrogen sulfide 7,12 .…”
Section: Introductionmentioning
confidence: 99%